2014
DOI: 10.1111/febs.13035
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription 3 and the phosphatidylinositol 3‐kinase regulatory subunits p55α and p50α regulate autophagy in vivo

Abstract: Mammary gland involution involves a process that includes one of the most dramatic examples of cell death in an adult mammalian organism. We have previously shown that Stat3 regulates a lysosomal pathway of cell death in the first 48 hours of involution and induces lysosome leakiness in mammary epithelial cells. Interestingly, Stat3 is associated also with the striking induction of autophagy which occurs concomitantly with cell death, presumably as a transient survival mechanism. The PI3 Kinase regulatory subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Thus STAT3-mediated upregulation of CTSB and CTSL enhances cell death by lysosomal membrane permeabilization (LMP) during mammary gland involution, 45 whereas LMP impairs autophagy because the autophagy flux requires functional lysosomes. 46 As described above, nuclear STAT3 executes anti-autophagic functions by upregulating negative regulators of autophagy such as BCL2, BCL2L1, MCL1, PIK3R1/p55a, and PIK3R1/p50a, or by downregulating essential autophagy genes such as BECN1 and PIK3C3. However, STAT3 also executes its pro-autophagic function by modulating the hypoxic expression of HIF1A (hypoxia inducible factor 1, a subunit [basic helix-loop-helix transcription factor]) and BNIP3.…”
Section: Stat3 In Autophagymentioning
confidence: 98%
See 1 more Smart Citation
“…Thus STAT3-mediated upregulation of CTSB and CTSL enhances cell death by lysosomal membrane permeabilization (LMP) during mammary gland involution, 45 whereas LMP impairs autophagy because the autophagy flux requires functional lysosomes. 46 As described above, nuclear STAT3 executes anti-autophagic functions by upregulating negative regulators of autophagy such as BCL2, BCL2L1, MCL1, PIK3R1/p55a, and PIK3R1/p50a, or by downregulating essential autophagy genes such as BECN1 and PIK3C3. However, STAT3 also executes its pro-autophagic function by modulating the hypoxic expression of HIF1A (hypoxia inducible factor 1, a subunit [basic helix-loop-helix transcription factor]) and BNIP3.…”
Section: Stat3 In Autophagymentioning
confidence: 98%
“…STAT3 suppresses autophagy in mammary gland cells by directly upregulating the PIK3R1/ p55a and PIK3R1/p50a (phosphoinositide-3-kinase, regulatory subunit 1 [a], p55a and p50a isoforms), which function as inhibitors of PIK3R1/p85a-mediated autophagy. 46 In addition, STAT3 transcriptionally enhances the expression of CTSB (cathepsin B) and CTSL (cathepsin L), possibly through the downregulation of Serpina3g, a known target of NFKB1 in memory T cells. 45 STAT3 can inhibit the transcriptional activity of NFKB1 by binding to NFKB1 and RELA, subsequently downregulating its target genes, including Serpina3g.…”
Section: Stat3 In Autophagymentioning
confidence: 99%
“…Nuclear STAT3 executes antiautophagic functions by upregulating negative regulators of autophagy such as BCL2, BCL2L1, MCL1, PIK3R1/p55 α and PIK3R1/p50 α . 76, 77, 78 Furthermore, STAT3 disrupts the formation of the pro-autophagic BCN1/PI3K-III complex by recruiting histone deacetylase 3 (HDAC3) to the promoter of BECN1 and repressing its expression. During EMT Integrin profiles and Integrin-ECM contacts undergo profound reorganization (Figure 4).…”
Section: Shared Signaling Pathways and Molecular Mediatorsmentioning
confidence: 99%
“…In the absence of active STAT5, a loss-of-function of STAT3 or its upstream regulator JAK1 significantly extends the functional competence of secretory epithelial cells and causes a delay in cell death and mammary gland remodeling (Chapman et al, 1999; Sakamoto et al, 2016b). The activation of STAT3 enhances the expression of p50α/p55α, and the analysis of an isoform specific knockout mouse model revealed that these smaller PI3 kinase regulatory subunits are involved in the programmed death of mammary epithelial cells (Figure 1), possibly through upregulation of cathepsin L (Pensa et al, 2014b) or though inhibition of autophagy (Pensa et al, 2014a). The model previously proposed by Abell et al (2005) that p50α and p55α inhibit the p85α/p110α PI3K holoenzyme and AKT1 needs to be revisited since the loss of active STAT5 during the onset of involution causes a swift decline in p85α, p110α, and AKT1 expression.…”
Section: Jak2/stat5 Signaling Promotes the Survival Of Mammary Epithementioning
confidence: 99%